Spatial learning of female mice: a role of the mineralocorticoid receptor during stress and the estrous cycle - Ter Horst, Judith P.; Kentrop, Jiska; Arp, Marit; Hubens, Chantal J.; de Kloet, E R.; Oitzl, Melly S. (Frontiers in Behavioral Neuroscience, 2013)
Corticosterone facilitates behavioral adaptation to a novel experience in a coordinate manner via mineralocorticoid (MR) and glucocorticoid receptors (GR). Initially, MR mediates corticosterone action on appraisal processes, risk assessment and behavioral flexibility and then, GR activation promotes consolidation of the new information into memory. Here, we studied on the circular holeboard (CHB) the spatial performance of female mice with genetic deletion of MR from the forebrain (MRCaMKCre) and their wild type littermates (MRflox/flox mice) over the estrous cycle and in response to an acute stressor. The estrous cycle had no effect on the spatial performance of MRflox/flox mice and neither did the acute stressor. However, the MRCaMKCre mutants needed significantly more time to find the exit and made more hole visit errors than the MRflox/flox mice, especially when in proestrus and estrus. In addition, stressed MRCaMKCre mice in estrus had a shorter exit latency than the control estrus MRCaMKCre mice. About 70% of the female MRCaMKCre and MRflox/flox mice used a hippocampal (spatial, extra maze cues) rather than the caudate nucleus (stimulate-response, S-R, intra-maze cue) strategy and this preference did neither change over the estrous cycle nor after stress. However, stressed MRCaMKCre mice using the S-R strategy needed significantly more time to find the exit hole as compared to the spatial strategy using mice suggesting that the MR could be needed for the stress-induced strategy switch toward a spatial strategy. In conclusion, the results suggest that loss of MR interferes with performance of a spatial task especially when estrogen levels are high suggesting a strong interaction between stress and sex hormones.